2018
DOI: 10.2147/ppa.s159707
|View full text |Cite
|
Sign up to set email alerts
|

Patient engagement in type 2 diabetes mellitus research: what patients want

Abstract: BackgroundAs patients are the ultimate stakeholder in their health, their perspectives should be included along with researchers, providers, and funders of research design, execution, and interpretation. Despite the high prevalence of type 2 diabetes mellitus (T2DM), patients are rarely directly included in these decisions.PurposeWe sought to determine areas of research most important to patients with T2DM, identify ways through which patients with T2DM want to engage in research, and evaluate online patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…However, using the PFAC model is only one approach. Other opportunities exist that may allow for greater outreach and an increase in the diversity of engaged stakeholders, without necessarily requiring in‐person meetings: for instance, the use of e‐advisors and online communities such as the “Patients Like Me” collaborative that has informed type II diabetes research …”
Section: Discussionmentioning
confidence: 99%
“…However, using the PFAC model is only one approach. Other opportunities exist that may allow for greater outreach and an increase in the diversity of engaged stakeholders, without necessarily requiring in‐person meetings: for instance, the use of e‐advisors and online communities such as the “Patients Like Me” collaborative that has informed type II diabetes research …”
Section: Discussionmentioning
confidence: 99%
“…13 Another study carried out in a closed online community also reported diabetes management as one of the main interests of individuals affected with type 2 diabetes. 31 In this new study, the proportion of posts on self-management in the same closed patient group reached 85%. Interestingly, in both studies, the posts on self-management also had the highest average number of comments.…”
Section: Discussionmentioning
confidence: 68%
“…A survey distributed to T2D patients found that the highest priority question is: ‘Can T2D be cured or reversed, what is the best way to achieve this and is there a point beyond which the condition cannot be reversed?’ 15 . Furthermore, patients most want to see T2D research conducted towards ‘managing T2D with comorbidities, controlling blood sugar levels, finding a cure and understanding causes of T2D’ 16 . When T2D patients were interviewed after a weight loss intervention study, 17 four themes emerged to form a patient narrative of cure for T2D.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Furthermore, patients most want to see T2D research conducted towards ‘managing T2D with comorbidities, controlling blood sugar levels, finding a cure and understanding causes of T2D’. 16 When T2D patients were interviewed after a weight loss intervention study, 17 four themes emerged to form a patient narrative of cure for T2D. The results were: ‘Building behavioural autonomy’ as a process of growing confidence to engage in health behaviours that are independent of those of other people.…”
Section: Introductionmentioning
confidence: 99%